PEMBELAJARAN BAHASA INDONESIA BERWAWASAN EKOLITERASI SEBAGAI MEDIA PEMBENTUKAN KARAKETER PEDULI LINGKUNGAN BAGI SISWA SEKOLAH DASAR - Isnanda, Romi; Gusnetti, Gusnetti; Sayuti, M; Syofiani, Syofiani; Rinaldi, Rio; Marsis, Marsis (Study program PGSD FKIP Universitas Bung Hatta, 2022)
The article contains the process of learning Indonesian in Elementary Schools (SD) with an ecoliteracy perspective. This is done on the basis that the government through the curriculum urges every citizen to be wise to the environment. Concretely, this is done in a planned manner at every level of education, especially at the elementary school (SD) level in Indonesian language subjects. The approach used is to use the method of content analysis (content analysis). The content analysis carried out is to describe and explain ecoliteracy-based language learning strategies in the form of using texts with ecological intelligence insight that can contribute to the character of caring for the environment. . language learning in elementary schools (SD). Based on the approach taken, the cultivation of an attitude of caring for the environment in elementary schools is carried out by using contextual texts, such as the content of intelligence on the environment. The text presented by the teacher is a condition of environmental damage caused by disobedient human behavior, such as throwing garbage in its place. The text presented certainly reflects a balance between the narrative of events and images that reflect the environment, such as floods and landslides. In principle, teachers must be able to explore how important it is to protect the surrounding environment.